2011
DOI: 10.2147/bctt.s21741
|View full text |Cite|
|
Sign up to set email alerts
|

Eribulin (Halaven): a new, effective treatment for women with heavily pretreated metastatic breast cancer

Abstract: Although metastatic breast cancer remains essentially incurable, many patients previously treated with an anthracycline, taxane, and capecitabine are relatively fit and keen to receive further therapy. Several drugs are used in this setting, but with little evidence of clinically relevant benefit, and none have previously shown improved survival. Eribulin (Halaven ® ) is a nontaxane tubulin-binding agent with a novel mode of action, and was recently approved by the European Medicines Agency and US Food and Dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…While simplified in structure compared to the natural product, its commercial chemical synthesis is nothing short of heroic with an overall molecular size of 731 daltons and 19 chiral centers. Eisai Pharmaceuticals in the US recently launched this agent under the product name Halaven®, and it is quickly finding utility in the treatment of drug refractory breast cancer (Menis and Twelves, 2011). …”
Section: Some Marine Drug Discovery Success Storiesmentioning
confidence: 99%
“…While simplified in structure compared to the natural product, its commercial chemical synthesis is nothing short of heroic with an overall molecular size of 731 daltons and 19 chiral centers. Eisai Pharmaceuticals in the US recently launched this agent under the product name Halaven®, and it is quickly finding utility in the treatment of drug refractory breast cancer (Menis and Twelves, 2011). …”
Section: Some Marine Drug Discovery Success Storiesmentioning
confidence: 99%
“…Following from this initial discovery, a variety of other anti-cancer drugs from marine invertebrates have been developed. These include for example; Halaven® (eribulin), used to treat metastatic breast cancer [75] and developed from the metabolite halichondrin B produced by the sponge Halichondria okadai [76,77], and ADCETRIS® (brentuximab vedotin, SGN-35) used for the treatment of Hodgkin lymphoma and anaplastic large cell lymphoma Structures of compounds with pharmacological activity produced by microbes: (a) nojirimycin [47,60], an exemplar β-glucosidase inhibitor; (b) Yondelis ® (ecteinascidin 743/trabectedin) [61][62][63], (c) smenothiazole A [49,64], and (d) smenothiazole B [49,65], exemplar anti-tumorigenic compounds; (e) manzamine A [66,67], an exemplar multi-functional drug; (f) kocurin [55,68], an exemplar antibiotic; (g) norharman (a β-carboline alkaloid) [51,57,69], an exemplar anti-microbial compound; (h) zeaenol (a resorcylic acid lactone) [59,70], an exemplar anti-fungal compound.…”
Section: Yondelis® Smenamides and Smenothiazoles: Compounds With Anmentioning
confidence: 99%
“…Following from this initial discovery, a variety of other anti-cancer drugs from marine invertebrates have been developed. These include for example; Halaven ® (eribulin), used to treat metastatic breast cancer [75] and developed from the metabolite halichondrin B produced by the sponge Halichondria okadai [76,77], and ADCETRIS ® (brentuximab vedotin, SGN-35) used for the treatment of Hodgkin lymphoma and anaplastic large cell lymphoma [78], and developed via antibody chimerisation through the addition of a dipeptide linker to the potent antitubulin agent dolastatin 10 from the sea hare Dolabella auricularia [79,80].…”
Section: Yondelis ® Smenamides and Smenothiazoles: Compounds With mentioning
confidence: 99%
“…These are massive, amorphous sponges with clearly separated inner and outer skeletons consisting of bundles of spicules arranged in a seemingly random pattern. Eisai Pharmaceuticals in the United States recently launched this agent under the product name Halaven, and it is quickly finding utility in the treatment of drug refractory breast cancer [317]. During the course of synthetic efforts in this area, it was found that the macrocyclic portion of the molecule was responsible for the potent biological activity, and this could be enhanced through modification of the macrolactone functionality to a macrocarbocyclic ketone, giving rise to eribulin [316].…”
Section: Plant and Marine Sourcesmentioning
confidence: 99%